Evaluation of administration and use of antihypertensive drugs in severe preeclampsia patients at X General Hospital in Jakarta - Simatupang, Abraham; Ida Bagus Sutha Dwipajaya (Indonesian Journal of Pharmacology and Therapy, 2021)
The high number of maternal mortality rate (MMR) is still a problem in Indonesia. Three ethyologies of maternal death are infection (12%), hypertension in pregnancy (25%) and bleeding (30%). Pre-eclampsia as a form of hypertension during pregnancy requires antihypertensive drug therapy. Rationality assessment for any kinds of pharmacotherapy is based on the right indication, the right medicine, the right patient, and the right dose. The main indication for antihypertensive medication in pregnancy is applied to the mother’s in preventing cerebrovascular disease. The aim of this study was to evaluate the characteristics, patterns and accuracy of the administration and use of antihypertensive drugs in patients with severe preeclampsia at X General Hospital in Jakarta in 2018. It was a non-experimental study with a descriptive and retrospective design using medical records. Administration and use of antihypertensive drugs in patients with severe preeclampsia at the X General Hospital in Jakarta showed 91.9% right indication, 86.72% right drug, 96.9% right patient and only 5.26% right dose with 4.0% accuracy of rational administration and use of drugs. In conclusion, the right dose in the management of patients with severe preeclampsia in X General Hospital in Jakarta is still low. Further training and close monitoring and evaluation on the rational use of antihypertension in severe preeclampsia is needed.